Challenges Faced by Nurses Working at Tertiary Cancer Hospital, Nepal - Sushila Koirala,; Anita Sharma, (Journal of Balkumari College, 2025)
Background: Challenges faced by nurses are the issues that occur while providing care to the patients. Nurses dealing with cancer patients have more stressors than other nurses providing care for general patients. Thus, this study aims to identify the challenges faced by nurses who were working at tertiary cancer hospital of Nepal Materials and Methods: A quantitative cross-sectional study was carried out to identify the challenges faced by nurses who were working at B.P. Koirala Memorial Cancer Hospital (BPKMCH). The study was conducted among 90 nurses who had at least six months work experience selected through non-probability purposive sampling and the data was collected through a self- administered semi-structured questionnaire. Data were analyzed by using Statistical Package for Social Science (SPSS) version 22. Findings: The findings of the study revealed that most of the respondents had workplace and communication challenges. Major workplace challenges were shortage of staffs (83.3%) and problem of workload (67.8%). Likewise, major communication challenges were language barrier (81.1%) and problem with the breaking bad news (76.7%). Similarly, 66.7% of the respondents reported problem with dealing with the visitors of dying patients as the patient care challenge. Conclusion: This study concludes that nurses working at cancer hospital are facing various challenges specifically related to work place and communication and patient care challenges. Hence, concerned authority of hospital management should make strategic planning and implement measures to address and overcome the challenges faced by nurses to provide job satisfaction and morale so that it can help to provide quality nursing care to the cancer patients.